Calculation Driven Parametric Design of a Mechanical Assembly on the Example of a Hook Block - Filip Stanić; Daniel Miler; Matija Hoić (Tehnički Glasnik)
Parametric modeling is a common technology in numerous CAD software packages. One of the advantages of applying parametric modeling is the possibility of forming families of models that share a geometric structure with differences in dimensions. The user is left to generate a new set of dimensions. This paper presents an investigation of the possibility of upgrading the parametric modeling system with the calculation of the mechanical components in the form of a computer program. The user enters a set of operational requirements on the target mechanical assembly based on which the computer program calculates the needed dimensions of mechanical components to fulfill given requirements. The results of these calculations are used to parameterize the model. This approach is demonstrated using the example of a Hook Block model developed within the 3DExperience (3DX).